Switchable solvent liquid-phase microextraction-gas chromatography-quadrupole isotope dilution mass spectrometry for the determination of 4-n-nonylphenol in municipal wastewater - Erarpat, Sezin; Bodur, Suleyman; Chormey, Dotse Selali; Bakirdere, Sezgin (ELSEVIER SCIENCE BV, 2019)
Quadrupole isotope dilution mass spectrometry ((IDMS)-M-4) and switchable solvent based liquid phase micro-extraction (SS-LPME) were combined to determine 4-n-nonylphenol (NP) in municipal waste water samples at trace levels. In this method, SS-LPME served as a preconcentration technique to reach trace levels for NP, while (IDMS)-M-4 was used as a measurement technique to improve accuracy and precision of the proposed method. A response surface methodology was performed to investigate the key parameters of SS-LPME method. Analysis of variance (ANOVA) was employed to assess the main experimental parameters and their interactions each other. Three calibration blends and one waste water sample blend were prepared with NP and 4-n-nonylphenol-D8 (NP-D8) for the application of SS-LPME-(IDMS)-M-4. All the system parameters were optimized to improve the accuracy and detection power. Recovery of the SS-LPME-(IDMS)-M-4 method for waste water spiked at 40 ng g(-1) was calculated as 101.5 +/- 0.4%. This result does not only establish good applicability of the method to waste water, but also confirms the high accuracy and precision at a low concentration.
Keywords: 4-n-nonylphenol; Quadrupole isotope dilution mass spectrometry; Switchable solvent based liquid phase microextraction; Multivariate optimization; BISPHENOL-A; HYDROPHILICITY SOLVENT; SAMPLES; 4-NONYLPHENOL; NONYLPHENOL; FATE; 4-TERT-OCTYLPHENOL; DERIVATIZATION; SPECIATION; SINGLE; Chemistry